2023
DOI: 10.3390/ijms24097885
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Neurogenic Lower Urinary Tract Dysfunction after Spinal Cord Injury

Abstract: This article provides a synopsis of current progress made in fundamental studies of lower urinary tract dysfunction (LUTD) after spinal cord injury (SCI) above the sacral level. Animal models of SCI allowed us to examine the effects of SCI on the micturition control and the underlying neurophysiological processes of SCI-induced LUTD. Urine storage and elimination are the two primary functions of the LUT, which are governed by complicated regulatory mechanisms in the central and peripheral nervous systems. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 116 publications
(167 reference statements)
0
13
0
Order By: Relevance
“…In this study, the prevalence of urinary incontinence in Chinese patients with SCI was as high as 19.9% (n = 107). Urinary incontinence in patients with SCI is often caused by overactivity of the forced urinary muscles 30 . Overactivity of the detrusor muscle may lead to mucosal ischemia, and inadequate tissue perfusion affecting the natural protection of the mucosa by blood and reducing the release of inflammatory cells, thus promoting the proliferation of microorganisms 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of urinary incontinence in Chinese patients with SCI was as high as 19.9% (n = 107). Urinary incontinence in patients with SCI is often caused by overactivity of the forced urinary muscles 30 . Overactivity of the detrusor muscle may lead to mucosal ischemia, and inadequate tissue perfusion affecting the natural protection of the mucosa by blood and reducing the release of inflammatory cells, thus promoting the proliferation of microorganisms 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TRP channels such as TRPA1 and TRPV1, which are predominantly expressed in C-fiber afferent neurons, are upregulated in L6-S1 DRG or the bladder mucosa in animal models of SCI-induced LUTD and that C-fiber bladder afferent hyperexcitability contributes to DO in animal models of SCI. 18 Moreover, it has been demonstrated that activation of CB1 receptors by the intravesical instillation of a CB1 agonist or by the reduction of degradation of endocannabinoids in FAAH knockout mice suppressed bladder activity enhanced by nerve growth factor. 19 Moreover, CB2 receptor stimulation by a CB2 agonist reportedly inhibited the mechanosensitivity of bladder mucosal capsaicin-sensitive C-fiber afferents in the organ bath study.…”
Section: Discussionmentioning
confidence: 99%
“…Small rodents, such as rats and mice, have formed the foundation of our understanding of the neural control of micturition and the mechanisms underlying the impairment of LUT function after SCI, in part because their bladders have been well-characterized by both in vitro and in vivo experiments [ 20 , 123 , 142 , 143 , 144 , 145 ]. Their lifespan of about 1–2 years means that it is also feasible to evaluate the effects of chronic SCI [ 118 ].…”
Section: Cystometric Findings In Animal Models Of Scimentioning
confidence: 99%
“…Moreover, the quantitative observation of urinary tract function before and after SCI—in the same individual—is effectively impossible with human patients. Animal models are therefore critical for investigating the in vivo consequences of NLUTD, and they allow for the development and testing of novel therapeutic approaches and understanding the complex pathophysiology of a neurogenic bladder [ 20 ]. Given the importance of animal models, clinical UDS has been adapted to a wide variety of animal species.…”
Section: Introductionmentioning
confidence: 99%